Rapid and Integrated Agriculture Risk Management Review for Brazil : Towards an Integrated Vision - World Bank (World Bank, Brasilia, 2019)
The agriculture sector of Brazil faces a large number of risks linked to the productive process, which has led to substantial losses to the country in the past years. An adequate and integrated management of those risks can leave farmer incomes less exposed to losses, benefiting the sector and the country as a whole. Therefore, given the always-present resource limitation, it is important to maximize the economic returns of agriculture risk management actions. Brazil built important agriculture risk management policies and programs, but there are several signs that it is possible to improve their efficiency of effectiveness with more coordination and a prioritization in the treatment of gaps and opportunities. The objective of this work was to undertake a rapid and integrated review of agriculture risk management in Brazil, identifying gaps and opportunities for improving current public policies and programs at the federal level in the short and long term. Beyond potential improvements in specific agriculture risk management policies and programs, an improved coordination and integration of current tools can reduce the risk profile of the sector. In this context, the World Bank, Brazilian Agriculture Research Company (Embrapa ) and Ministry of Agriculture, Livestock and Supply (MAPA) put forward a rapid and integrated review of agriculture risk management in Brazil. This rapid review suggests that actions that seek the implementation of an integrated agriculture risk management vision are supported by society at large and by the public sector’s interest. Finally, planning requires the need for a stable institutional framework, which calls for a national plan and an agriculture law, with at least a five-year horizon and that must consider not only the agriculture risk management issues, but also rural development ones.